2000
DOI: 10.1016/s1044-0305(99)00134-8
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-assisted laser desorption/ionization mass spectrometry, enzymatic digestion, and molecular modeling in the study of nonenzymatic glycation of IgG

Abstract: The glycation-induced functional change of immunoglobulins is of particular interest. The glycation levels of IgG in 10 healthy subjects and 20 diabetic patients with different degrees of metabolic control were studied by matrix-assisted laser desorption/ionization (MALDI) mass spectrometry. It reveals the number of glucose molecules that have condensed on the protein, which range from 1 to 5 for healthy subjects, from 5 to 9 for well controlled diabetic patients, and from 10 to 25 for poorly controlled ones. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 26 publications
2
58
1
1
Order By: Relevance
“…The nonenzymatic glycation of immunoglobulins as a result of hyperglycemia could result in low antigen and receptor binding capacities of these antibodies. It is therefore likely that despite comparable titers, the functionality of the antibody is compromised in diabetics compared to nondiabetics (25,26). Contrary to our findings with PspA, we observed comparable titers of antibodies to all eight capsular polysaccharides tested in individuals with and individuals without diabetes.…”
Section: Discussioncontrasting
confidence: 99%
“…The nonenzymatic glycation of immunoglobulins as a result of hyperglycemia could result in low antigen and receptor binding capacities of these antibodies. It is therefore likely that despite comparable titers, the functionality of the antibody is compromised in diabetics compared to nondiabetics (25,26). Contrary to our findings with PspA, we observed comparable titers of antibodies to all eight capsular polysaccharides tested in individuals with and individuals without diabetes.…”
Section: Discussioncontrasting
confidence: 99%
“…Glycation of IgG is of special interest due to its influence on the functionality of immunoglobulin's and overall immunocompetence. Several studies showed the extent of glycation of IgG and its influence on the biological functionality of IgG [5][6][7][8][9][10][11][12][13], but the immunological role of AGEs damage IgG (AGE-IgG) in patients with type 1 DM is still not fully understood. Proper extensive clinical investigation of this aspect with a high level of confidence are needed.To meet this need, we hypothesized that AGE-IgG helps to initiate autoimmunity in type 1 diabetes mellitus patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is now becoming increasingly evident that glycation may also compromise the biological activity of functional proteins, including glucose-6-phosphate dehydrogenase (13), aldehyde reductase (14), glutathione reductase (15), Cu-Zn superoxide dismutase (16,17), HDL (18), and both IgM and IgG (19,20). Studies also suggest that glycation of ␤-cell proteins may contribute to defective insulin secretion, and glucokinase has been implicated (21,22).…”
mentioning
confidence: 99%